Laparoscopic management of congenital splenic cyst with intracystic bleed - Shaik Mohammed Waseem; Jayanth Bannur Nagaraja; Nairuthya Shivathirthan (Apollo Medicine, 2020)
Splenic cysts can be congenital, vascular, neoplastic, inflammatory, and posttraumatic contributing to 30%–40% of the total splenic lesions.Congenital splenic cysts are usually asymptomatic and are rarely seen in routine surgical practice. Due to lack of typical clinical presentation, they are discovered incidentally. Splenic congenital cysts constitute approximately 10% of total cysts. Primary (true) cysts make up approximately 20% of all types of cysts which occur in spleen. Epidermoid cysts are the rarest, which comprise only 10% of benign, nonparasitic cysts which occur in the spleen. Here, we present a case of 28-year-old female who presented to the hospital with vague upper abdominal pain and on clinical and radiological investigations was diagnosed as a case of congenital epidermoid cyst of the spleen with evidence of intracystic bleed which was managed laparoscopically.